The Effect of Digital Banking on Banking Performance during the Covid-19 Pandemic - Sri Utami Nunik Chairita; Suharnomo Suharnomo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effect of digital banking on banking performance during the covid-19 pandemic. The research method that is considered appropriate for this research is descriptive quantitative with a cross sectional design of hypothesis testing using linear regression. There is a significant influence between digital banking (DB) on the return of assets at conventional banks in Indonesia during the COVID-19 pandemic, there is a significant effect between digital banking (DB) on the return on equity at conventional banks in Indonesia during the COVID-19 pandemic and There is a significant influence between digital banking (DB) on operating costs of operating income at conventional banks in Indonesia during the COVID-19 pandemic. In implementing digital banking innovation, it is hoped that banks will be able to implement risk management to deal with various risks with digital banking innovation.